LGBTQI workbook for CBT - Schott, Erik (New York, NY : Routledge, 2021)
Cognitive-Behavioral Therapy (CBT) is one of the most popular evidence-based interventions in the world, but little has been done to explore how it affects different groups of people, such as the lesbian, gay, bisexual, transgender, queer, and intersex (LGBTQI) community. The LGBTQI Workbook for CBT is filled with hands-on, practical perspectives for readers who are seeking a new point-of-view or for clinicians and students seeking additional tools, competence, and humility when working with sexual and gender minorities. The workbook focuses on skill building and addresses techniques for personal selfassessment, cognitive and behavioral activation, psychoeducation, and therapist resources. Incorporating structured learning tools to promote professional responsibility as well as ethically driven and evidence-based practices, this text aims to promote empowerment. Applied activities are available in multiple reproducible worksheets and handouts to utilize in session, in the classroom, in the field, and in life. The LGBTQI Workbook for CBT is an invaluable resource for interested members of the LGBTQI community, beginner or experienced clinicians, and students working with sexual and gender minority clients. It is an excellent supplementary text for graduate students in social work, psychology, nursing, psychiatry, professional counseling, marriage and family therapy, and other healing professions such as medicine, acupuncture, or physical therapy.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Sexual minorities -- Psychology; Sexual minorities -- Psychology -- Problems, exercises, etc; Cognitive therapy -- Problems, exercises, etc; SOCIAL SCIENCE / Sociology / General